Ordinal item response theory: Mokken scale analysis - Schuur, Wijbrandt van (Sage University papers / Quantitative applications in the social sciences, 2011)
"Ordinal Item Response Theory is volume 169 in the SAGE Series "Quantitative Applications in the Social Sciences" (QASS). The of Ordinal Item Response Theory is referred to throughout many other QASS titles and fills a gap between the more classical topics of undimensional scaling, test theory, principal component and factor analysis. In addition, this volume also discusses parametric item response theory and latent class analysis. This monograph is less technical than many books on the market and is best suited for an introductory course in social science measurement"--